2021
DOI: 10.1002/cbin.11669
|View full text |Cite
|
Sign up to set email alerts
|

ETV4 transcriptionally activates HES1 and promotes Stat3 phosphorylation to promote malignant behaviors of colon adenocarcinoma

Abstract: Colon adenocarcinoma (COAD) is the commonest type of colorectal cancer with high morbidity and mortality worldwide. ETS variant 4 (ETV4) is a member of the ETS transcription factors and is frequently involved in the progression of many cancers. This study focused on the relevance of ETV4 to the progression of COAD. ETV4 was highly expressed in the collected COAD tissues and acquired cells and indicated advanced Dukes staging in patients. Knockdown of ETV4 in COAD cells weakened proliferation, migration, invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…ETV4 has been reported to activate B3GNT3 and mediate TGF-β1 signal transduction, thereby promoting EMT in liver cancer (38). In colon adenocarcinoma, knocking out ETV4 has been reported to reduce EMT (39), which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…ETV4 has been reported to activate B3GNT3 and mediate TGF-β1 signal transduction, thereby promoting EMT in liver cancer (38). In colon adenocarcinoma, knocking out ETV4 has been reported to reduce EMT (39), which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In CRC, the functions of ETS family members differ. For example, ETV1, ETV5, ETV4, EHF, ELK1, ETL4, ETS1, ETS2, and ERG act as tumor promoters accelerating angiogenesis in CRC (Cheng et al 2019 ; Li et al 2016 ; Ma et al 2021a , b ; Meng et al 2019 ; Wang et al 2020a , b , c ; Wang et al 2020a , b , c ; Yao et al 2021 ; Zhu et al 2020 ). In contrast, SPIB, SPDEF, and ELF5 exert anti-CRC effects (Ma et al 2021a , b ; Noah et al 2013 ; Zhao et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 The HES1 has been reported overexpressed and acted as oncogenic roles in various types of cancers, such as colon adenocarcinoma, pancreatic carcinoma, glioblastoma, oral squamous cell carcinoma, cutaneous T-cell lymphoma and so on. 11,13,[20][21][22] Li et al 23 reported that in triple-negative breast cancer, the expression of HES1 may promoted the invasion of cancer cells, whereas knockdown the HES1 reduces the self-renewal and population of cancer stem cells and the proliferation of cancer cells. All of these findings suggest that HES1 have a crucial role in the regulation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The HES1 is a transcript factor regulated by NOTCH, Wnt, and Hedgehog signaling pathways, which plays a crucial role in the regulation of cell cycle, proliferation, differentiation, and various cancers 19 . The HES1 has been reported overexpressed and acted as oncogenic roles in various types of cancers, such as colon adenocarcinoma, pancreatic carcinoma, glioblastoma, oral squamous cell carcinoma, cutaneous T-cell lymphoma and so on 11,13,20–22 . Li et al 23 reported that in triple-negative breast cancer, the expression of HES1 may promoted the invasion of cancer cells, whereas knockdown the HES1 reduces the self-renewal and population of cancer stem cells and the proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%